REPRESENTASI QUARTER LIFE CRISIS DALAM LIRIK LAGU “PERJALANAN” KARYA DANAR WIDIANTO (ANALISIS SEMIOTIKA ROLAND BARTHES) - Aulia Zahra Rizquita; Silvina Mayasari; Sari Ekowati (An Nafi': Multidisciplinary Science, 2025)
The phenomenon of a quarter-life crisis, marked by uncertainty, anxiety, and identity exploration among young adults, has become increasingly significant in popular culture. This study aims to reveal the representation of the quarter-life crisis in the lyrics of “Perjalanan” by Danar Widianto using Roland Barthes’ semiotic analysis. A qualitative interpretative method was applied, supported by data collection techniques such as observation, in-depth interviews with the songwriter, and documentation. The analysis involved Barthes’ three levels of signification—denotation, connotation, and myth—combined with Stuart Hall’s representation theory. The findings show that the lyrics of “Perjalanan” reflect personal experiences of life’s uncertainties, hope, perseverance, and self-reflection, which are closely associated with the characteristics of a quarter-life crisis. The connotative meaning emphasizes the importance of setting goals, overcoming challenges, and not giving up along life’s journey. Moreover, the song conveys myths about life’s struggles and the belief that hardships are temporary. Beyond its portrayal of a quarter-life crisis, the lyrics also embed values of romanticism, religiosity, and optimism that deliver a strong moral message to listeners.